IMG-12. CHARACTERISATION OF MODELS OF H3F3A_G34R/V MUTANT PAEDIATRIC GLIOBLASTOMA IN VIVO USING MAGNETIC RESONANCE IMAGING. (4th December 2020) - Boult, Jessica; Bjerke, Lynn; Fofana, Mariama; Vinci, Maria; Molinari, Valeria; Mackay, Alan; Temelso, Sara; Box, Gary; Eccles, Suzanne; Carcaboso, Angel; Castro, Maria; Waanders, Angela; et al.
Abstract: Approximately 15% of paediatric/young adult cerebral hemispheric glioblastomas (pGBM) harbour G34R/V mutations in H3F3A, encoding the histone H3.3 variant. Development of novel therapeutic interventions demands models that accurately recapitulate this subset of disease and sensitive imaging methods with which to study tumours in situ . Three H3F3A _G34R primary-patient-derived cultures, alongside established cell-line KNS42 ( H3F3A _G34V), were implanted orthotopically in immunocompromised mice. KNS42 ( TP53 _R342*) tumours were clearly detectable using T2- weighted (T2 w)-MRI, enhanced following contrast agent administration, indicating impaired blood-brain barrier (BBB) integrity, and demonstrated minimal invasion. OPBG_GBM_001 cells ( TP53 _89-90X, ATRX _II2133-2144X) formed infiltrative tumours that were hyperintense on T2 w-MRI and demonstrated contrast-enhancement suggestive of heterogeneous BBB integrity. HSJD_GBM_002 cells ( TP53 _P278T, ATRX _R666*) spread diffusely throughout the brain with their full extent typically not discernible by T2 w-MRI, the BBB also remaining intact. No evidence of CHOP_GBM_001 tumour was detected by MRI 11months post-implantation. Immunocompetent syngeneic models using tumour cells induced by mutations modelling hemispheric pGBM (NRAS/shP53/shATRX±H3.3G34R) are being explored. Fast growing heterogeneous lesions with variable contrast-enhancement were identified; the H3.3G34R mutation conferred longer median survival (2 clones:25/28days, control:14days). These models have the advantage of an intact immune system and short latency for initial efficacy studies. Primary pGBM cells yield tumours that are more representative of the spectrum of clinical disease; variable hyperintensity on T2 w-MRI corresponding to cellular density, with diffusely infiltrative disease less clearly definable, a paucity of oedema and a range of contrast-enhancement. Pathological features including giant multinucleated cells, and mitotic figures were also evident.